REGIONALIZATION OF THE IDF CURVES FOR THE PROVINCES OF SANTO DOMINGO DE LOS TSACHILAS AND ESMERALDAS - RODRIGUEZ SANTOS, JOSUE EDILBERTO; CORAPI, PIETRO; MOYA CHAVEZ, LUIS; CEDEÑO ESPINOZA, LILIBETH; PEÑAFIEL DIAZ, SARA (LACCEI, 2025)
In this study, two methodologies were compared for the regionalization of precipitation data in the provinces of Esmeraldas and Santo Domingo de los Tsáchilas. 40 meteorological stations were initially selected, but 32 were used due to data availability. The main objective was to determine which methodology offered greater precision in the evaluated models.Process 1, based on the methodology of Nuñez Neira and Corapi, was compared with process 2, developed according to Velasco Ramos and Garaicoa Velásquez. The latter stood out for its comprehensive approach, which included the identification and correction of atypical data using the Hydrognomon program, as well as the adjustment of distributions for different return periods. Although the interpolation methods applied in process 2, such as Inverse Distance Weighted (IDW) and Ordinary Kriging (KO), presented a greater relative error than in process 1, the robustness of process 2 in data management and correction of anomalous values ​​turned out to be a decisive factor for their choice.Another advantage of process 2 was the implementation of the US method for estimating missing data, which added reliability to the results obtained. In conclusion, despite the error limitations in the interpolation methods, process 2 was considered more suitable due to its comprehensive approach and its ability to handle data accurately, detecting and correcting irregularities. These results provide a more reliable tool for the regionalization of precipitation in the study area, thus improving the basis for future hydrological research.